Assessment on surface integrity in electrochemical grinding of AISI 304 - Mohammad Yazdani; Amir Rasti (Heliyon)
Electrochemical grinding (ECG) offers advantages such as burr-free and stress-free material removal. Despite its proven potential, limited research has addressed the comprehensive effects of key process parameters on the surface integrity of AISI 304 stainless steel, particularly for applications requiring high-quality finishes, such as medical components. This study bridges this gap by systematically investigating the influence of ECG key parameters including voltage, rotational speed, and electrolyte concentration on main surface integrity parameters including current density, surface roughness, microhardness, and surface texture. Total of 20 experiments were carried out following a Response Surface Methodology (RSM) design, incorporating five levels of variation for the parameters of electrolyte concentration, voltage, and grinding wheel speed. Results revealed that voltage and electrolyte concentration were the dominant factors affecting current density, increasing it by 368 % and 241 %, respectively, while higher rotational speeds decreased it by 44.5 % due to reduced contact time and electrolyte removal. Surface roughness decreased by up to 65 % in the perpendicular direction as concentration and voltage increased, but higher voltages led to over-etching, increased the surface roughness. Electrolyte concentration and voltage also reduced surface microhardness by 10–14 % through intensified corrosion, while higher wheel speeds increased microhardness due to enhanced mechanical removal. The maximum variation for in-depth microhardness extended up to a depth of 40 μm below the surface. Surface texture analysis also revealed more uniform pitting across the surface at higher concentrations, indicating more consistent material dissolution. However, at higher voltages, deep pitting emerged, raising surface roughness.